MODERN APPROACH TO DEFINING INTERPRETER'S COMPETENCE IN CONSECUTIVE TRANSLATION - Олена Світлична (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The article analyzes modern approach to the problem of giving definition to the concept of interpreter's competence in consecutive translation. The author reveals existing approaches to the preparation of students majoring in interpreting and views users' needs, expectations and quality assurance for interpreting process. The article describes the concept of 'interpreter's competence' as a compound category consisting of a complex of diversified skills and knowledge, including special, subject and background one, enabling an interpreter to fulfil his functions, and defines its components.